2010
DOI: 10.1111/j.1365-2605.2009.00964.x
|View full text |Cite
|
Sign up to set email alerts
|

Early effects of Sertoli cell‐selective androgen receptor ablation on testicular gene expression

Abstract: Evidence from several models of hormone depletion and/or replacement and from knockout animals points to a key role of androgens in the control of spermatogenesis. In testes of mice with a Sertoli cell-selective ablation of the androgen receptor (SCARKO), transcriptional profiling, using microarray technology, revealed that, already on postnatal day 10,692 genes are differentially expressed compared with testes of control mice. Further evaluation of a subset of these genes by quantitative RT-PCR suggested that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 48 publications
4
50
0
1
Order By: Relevance
“…Prior ablation of the germ cells with busulphan, which does not significantly affect Leydig cell activity (O'Shaughnessy et al 2008b), removed the most androgen-dependent cell population from the testis but significant changes in the remaining Sertoli cells and PTMCs would still be expected following the loss of androgen stimulation. However, any reduction in expression in these cells might be expected to be delayed, and it should be noted that expression of Rhox5, Cldn11, Drd4 and Eppin, putative androgen-dependent transcripts in the mouse (Lindsey & Wilkinson 1996, O'Shaughnessy et al 2007, Hu et al 2010, Willems et al 2010, did not show any change up to 20d following EDS treatment (not shown). In contrast, Tubb3 and Cyp26b1, also proposed to be androgen dependent in the mouse (O'Shaughnessy et al 2007, Willems et al 2010, did show reduced expression after EDS treatment but with complex patterns of change, quite distinct from the canonical Leydig cell genes (Supplementary Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior ablation of the germ cells with busulphan, which does not significantly affect Leydig cell activity (O'Shaughnessy et al 2008b), removed the most androgen-dependent cell population from the testis but significant changes in the remaining Sertoli cells and PTMCs would still be expected following the loss of androgen stimulation. However, any reduction in expression in these cells might be expected to be delayed, and it should be noted that expression of Rhox5, Cldn11, Drd4 and Eppin, putative androgen-dependent transcripts in the mouse (Lindsey & Wilkinson 1996, O'Shaughnessy et al 2007, Hu et al 2010, Willems et al 2010, did not show any change up to 20d following EDS treatment (not shown). In contrast, Tubb3 and Cyp26b1, also proposed to be androgen dependent in the mouse (O'Shaughnessy et al 2007, Willems et al 2010, did show reduced expression after EDS treatment but with complex patterns of change, quite distinct from the canonical Leydig cell genes (Supplementary Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…However, any reduction in expression in these cells might be expected to be delayed, and it should be noted that expression of Rhox5, Cldn11, Drd4 and Eppin, putative androgen-dependent transcripts in the mouse (Lindsey & Wilkinson 1996, O'Shaughnessy et al 2007, Hu et al 2010, Willems et al 2010, did not show any change up to 20d following EDS treatment (not shown). In contrast, Tubb3 and Cyp26b1, also proposed to be androgen dependent in the mouse (O'Shaughnessy et al 2007, Willems et al 2010, did show reduced expression after EDS treatment but with complex patterns of change, quite distinct from the canonical Leydig cell genes (Supplementary Table 1). Discrepancies between the published literature and the effects of EDS on these Leydig cell mRNA transcripts androgen-dependent transcripts may be due to species differences between rat and mouse (see below) or to other differences in the animal models used (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it was shown that Sertoli cell-selective KO of AR in mice led to infertility manifested by meiotic arrest (Chang et al, 2004;De Gendt et al, 2004). Furthermore, Sertoli cell-specific AR-KO mice displayed a defective BTB, which was associated with a reduced expression of claudin-11, ZO-1, occludin, and gelsolin but with a significantly enhanced expression of vimentin Willems et al, 2010a;Willems et al, 2010b). In addition, it was noted that Sertoli cell maturation and Sertoli cell polarization were also perturbed in these Sertoli cell-specific AR-KO mice, and that JAM-C (an apical ES marker that is also restricted to the apical ES) was shown to be significantly reduced (Willems et al, 2010a), illustrating that androgens are crucial to both apical and basal ES function.…”
Section: Tight Junction (Zonula Occludens) and Basal Ectoplasmic Specmentioning
confidence: 99%
“…While AR is not expressed in Sertoli cells during fetal development in the rodent or human, the PMC are the primary cells expressing the AR in the fetal testes (Chemes et al, 2008;Majdic et al, 1995;Shapiro et al, 2005;Willems et al, 2010). Having reduced Sertoli cell number in the testis of ARKO and Tfm mice, but no effect in SARKO, (Johnston et al, 2004;Scott et al, 2007;Tan et al, 2005) suggests a role for [ ( F i g .…”
Section: [ ( F I G _ 4 ) T D $ F I G ]mentioning
confidence: 91%